Pendampingan Pelatihan Berbicara Bahasa Inggris dengan Metode Pemberdayaan Berkelanjutan (Sustainable Empowerment) di Pondok Pesantren Minhajut Thullab - Ahmada, Adib; Mahmud, Moh.; Sangadah, Fatimatus (Jurnal Pengabdian Masyarakat (JUDIMAS), 2025)
This mentoring program aims to improve the quality of human resources (HR) among students at Minhajut Thullab Islamic Boarding School through English speaking education and training using the Sustainable Empowerment method. The activities implemented cover various aspects, including teaching English speaking skills such as trilingual MC, role play, and storytelling. The program was conducted with a participatory approach, actively involving students in every stage of the activities. Students were provided with continuous materials and practice, allowing them to apply their English speaking skills in supportive and relevant real-life contexts. Evaluations were conducted regularly to measure progress and provide constructive feedback to participants. The results of the program implementation showed a significant improvement in the students' English speaking abilities, both in terms of confidence and effective communication skills. Additionally, the participatory approach in this program also increased the students' motivation and engagement in the learning process. These findings indicate that this mentoring program is effective in achieving its goals and provides tangible benefits to Minhajut Thullab Islamic Boarding School, making it a potential model for similar programs in other boarding schools.